2013
DOI: 10.1007/s00006-013-0422-4
|View full text |Cite
|
Sign up to set email alerts
|

A Clifford Algebraic Framework for Coxeter Group Theoretic Computations

Abstract: Real physical systems with reflective and rotational symmetries such as viruses, fullerenes and quasicrystals have recently been modeled successfully in terms of three-dimensional (affine) Coxeter groups. Motivated by this progress, we explore here the benefits of performing the relevant computations in a Geometric Algebra framework, which is particularly suited to describing reflections. Starting from the Coxeter generators of the reflections, we describe how the relevant chiral (rotational), full (Coxeter) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…We therefore systematically factorise Coxeter versors of root systems in the Clifford algebra, which gives the eigenplanes and exponents algebraically. We briefly discuss the 2D case of the two-dimensional family of non-crystallographic Coxeter groups I 2 (n), followed by the three-dimensional groups A 3 , B 3 and H 3 [8], before discussing the higher-dimensional examples. The simple roots for I 2 (n) can be taken as α 1 = e 1 , α 2 = − cos π n e 1 + sin π n e 2 , which yields the Coxeter versor W describing the n-fold rotation encoded by the I 2 (n) Coxeter element via v → wv =W vW as…”
Section: The Coxeter Planementioning
confidence: 99%
See 2 more Smart Citations
“…We therefore systematically factorise Coxeter versors of root systems in the Clifford algebra, which gives the eigenplanes and exponents algebraically. We briefly discuss the 2D case of the two-dimensional family of non-crystallographic Coxeter groups I 2 (n), followed by the three-dimensional groups A 3 , B 3 and H 3 [8], before discussing the higher-dimensional examples. The simple roots for I 2 (n) can be taken as α 1 = e 1 , α 2 = − cos π n e 1 + sin π n e 2 , which yields the Coxeter versor W describing the n-fold rotation encoded by the I 2 (n) Coxeter element via v → wv =W vW as…”
Section: The Coxeter Planementioning
confidence: 99%
“…At the last AGACSE in 2012, I presented a new link between the geometries of three and four dimensions; in particular, I have shown that any reflection group in three dimensions induces a corresponding symmetry group in four dimensions, via a new Clifford spinor construction [8,9]. This connection had been overlooked for centuries (usually one assumes the larger groups are more fundamental) but the new construction derives all the exceptional phenomena in 4D-D 4 , F 4 and H 4 -via induction from the 3D symmetry groups of the Platonic solids A 3 , B 3 and H 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a reflection (continuous O(3) or the discrete subgroup, the full icosahedral group the Coxeter group H 3 ) corresponds to sandwiching with the versor A, whilst the versors single-sidedly form a multiplicative group (the Pin(3) group or the discrete analogue, the double cover of H 3 , which we denote Pin(H 3 )). In the conformal geometric algebra setup one uses the fact that the conformal group C(p, q) is homomorphic to SO(p + 1, q + 1) to treat translations as well as rotations in a unified versor framework [24,16,5,8,9]. [8,9] also discuss reflections, inversions, translations and modular transformations in this way.…”
Section: Clifford Versor Frameworkmentioning
confidence: 99%
“…Via an affine extension, the symmetry point group is augmented so that it can describe structures at different radial levels collectively (Dechant et al, 2012(Dechant et al, , 2013Dechant, 2014). It therefore lends itself to the modelling of carbon onions (Patera & Twarock, 2002;Twarock, 2002).…”
Section: Introductionmentioning
confidence: 99%